Kae Tempest e il potere dell’arte nella società dell’indifferenza (Altre Modernità, 2022)
Kae Tempest (London, 1985) is a poet, musician and spoken word performer whose texts are situated in the liminal space between poetry and music. As a consequence, performance is an integral part of their work and serves as a trait d’union between the two forms. This paper analyzes the poems Brand New Ancients (2013) and Let Them Eat Chaos (2016), which are set in today’s London. Here, the main issues of contemporary society – overexploitation of resources, gentrification, social inequalities – are the background of the ordinary lives of people pervaded by numbness and unhappiness. In On Connection (2020), their latest essay written during the first phase of Covid-19 pandemic, Tempest reflects on the social and political function of literature and on the need to find a sense of community through empathy.
Keywords: poetry; spoken word; performance; connection; Kae Tempest